Chaya (Cnidoscolus aconitifolius) as an alternative for pig feeding: Producción y Salud Animal - ambrano-Mendoza, Jessica Z (2024)
The objective of this research was to evaluate the influence of chaya (Cnidoscolus aconitifolius) as an alternative for pig feeding during the growth stage. Prior to the development of the experiment, a characterization of the dehydrated plant material was carried out. A total of four treatments were used with three levels of inclusion of chaya flour (10 (T1), 20 (T2) and 30 (T3)%) plus a control treatment (T0). Pigs of 43 days of age with an average weight of 12 kg were used. In each treatment, the final weight, weight gain, feed consumption and feed conversion during the growth stage were evaluated. The results were analyzed using the InfoStat statistical program. The behavior of the pigs showed better results in the final weight in the treatments T0 and T3 with a weight of 57.51 and 57.62 kg·pig-1, respectively. In the same way, better results were obtained in weight gain with values of 44.62 and 44.80 kg·pig-1. Food consumption was similar in each treatment, registering a consumption of 83.69 kg. On the other hand, feed conversion was statistically better in treatments T0 and T3, with a total of 1.83 kg, respectively. It is concluded that chaya meal in concentrations of 30% can be considered a viable alternative for feeding growing pigs.